SAT0247 Combined Hip Abduction Angle Measured by Using Iphone Compass Application; A Novel Measurement Tool to Assess Hip Mobility. (9th June 2015) - Yarkan, H.; Zengin, B.; Kenar, G.; Cetin, P.; Sari, I.; Onen, F.; Akkoc, N.
Abstract : Background: Intermalleolar distance (IMD) is a component of the Bath ankylosing spondylitis metrology index (BASMI) and measures abduction of the hips. New generations of smartphones are equipped with a gyroscope and an accelerometer which in combination with a smartphone's operating system or specific software applications can be used for various inclinometric functions. Objectives: The purpose of this study was to estimate the intra and inter-rater reliability of using iphone built in compass application, as compared to IMD in the assessment of hip abduction in patients with Ankylosing Spondylitis (AS). Methods: The study sample included 20 AS patients (6 females, 14 males) with a mean age of 47.8 (±10.2). BASMI scores were obtained from patient charts. Two examiners measured intermalleolar distance as the standard method at two different time points with the patient lying in a supine position. Then combined abduction of the hips angle (CAHA) was measured by iPhone compass application twice. To stabilize the iphone's position during measurements an iphone case and an elastic bandage with velcro patches were used. Intra-rater and inter-rater reliability were examined with intra-class correlation coefficients (ICC). The validity was assessed by Pearson Correlation analysis. Results: The mean BASMI score was 43 (±22.7). The mean scores for BASDAI, ASDAS and BASFI were 3.7 (±19.9), 2.9 (±0.96) and the 3.5 (±24.02), respectively. The mean IMD was 83.6 cm (±24.4) for rater 1 and 83.4cm (SD: 23.1) for rater 2. The mean CAHA was 51.2° (±18.3) for rater 1 and 55.6°(±20.5) for rater 2. We observed almost an excellent intra and inter-rater reliability for both methods (Table 1 ). CAHA measurements showed a strong correlation with IMD (r=0.74). Conclusions: The results of this study suggest that measurement of combined hip abduction angle using iphone, which is not to be affected by patients' height, can be used as a novel hip mobility measure. Disclosure of Interest: None declared